Strategi Kompetensi Profesional Kepala Madrasah Dalam Menyukseskan Kurikulum Merdeka Di Mts Al Ihsaniyah Desa Sarang Burung Jambi Luar Kota Muaro Jambi - Aswin; Abu Darim (Suria Academic Press, 2025)
This study aims to analyze and describe the role of the madrasah principal as a manager in developing teachers’ professional competence at MTS Al-Ihsaniyah, Sarang Burung Village, Muaro Jambi District, from the aspects of planning, implementation, supervision, and follow-up. This research adopts a qualitative approach using a case study design. Data sources include the principal, vice principals of curriculum and facilities, vice principal of student affairs and public relations, teachers, students, and the foundation’s supervisor. Informants were selected through purposive sampling. Data collection techniques involved observation, interviews, and document study. The research used inductive qualitative data analysis techniques. The findings show that : (1) Planning is carried out by the principal through forming a madrasah development team, involving members in formulating the vision, mission, and programs, planning programs based on needs, and aligning them with policy; (2) Implementation is carried out by optimizing the principal's duties, fostering a sense of shared responsibility and family principles, setting a motto for educators, executing the program, and maintaining a strong professional image; (3) Supervision is carried out by involving the foundation in overseeing programs, directly supervising program implementation, maintaining good communication, and identifying shortcomings; (4) Follow-up is done by giving full support, involving the foundation, analyzing programs, and providing facilities for implementation